USAGE OF 12 ANIMATION PRINCIPLES IN THE WAYANG KULIT PERFORMANCES - Tsai, Ming Hsin; Hapsari, Andi Tenri Elle (Yayasan Petra Harapan Bangsa, 2010)
Wayang Kulit has been known as one of the oldestanimation; however, there is no definitive methodology thatsupports the development process of these animation performancesthat we know nowadays. This paper aims to give an overview ofusing the famous 12 principles of animation in the Wayang Kulitperformance. A qualitative study of the Wayang KulitPerformances is described, aiming at finding the similaritiesbetween the traditional animation techniques and those techniquesused in this shadow puppet shows.